Monitoreo e identificación de cambios de la vegetación a lo largo del gradiente altitudinal en la zona baja del páramo de la Reserva Ecológica los Ilinizas. - Añarumba Ulloa, Johanna Lizeth (2023)
The objective of this research report was to determine through the collective brand analysis, This study was carried out along altitudinal gradient of the Ilinizas Ecological Reserve to determine possible variation of paramo vegetation, plotting eight transects between 4300 and 4550 masl with a altitudinal distance of 30 meters ascending within these 10 transects of 30 linear meters were made using a rectangular grid of 1 m^2 locating 10 plots randomly separated by a distance of 3 meters, species were classified using Braun Blanquet index with a 7 degree vegetation cover scale, basic environmental data were obtained for each sample, the graphs show that the vegetation is decreasing noticeably since the third transect with an altitude of 4360 meters due to cattle presence and the alteration of climatic changes, it has been observed that during transect 3, 4 and 5 the wealth is almost similar, there are two areas herbaceous paramo and dry paramo where the families with greater relative diversity are: Amblistegiaceae and Asteraceae. Simpson’s diversity index determined that all sites are diverse showing no dominance of single species, while comparative analysis across the Sorensen and Jaccard indices show that transects 5 and 6 are more similar, since they share same species by their range closer to 1, whereas PERMANOVA analysis found that all the transects are different from each others containing a minimum difference between plant communities and non- parametric analysis show that intersecting some transects getting the same community as on result 5 different communities. In turn, UICN conservation status of the found species at REI was reviewed, presenting 13 species in the Least Concern range, species in the Near Threatened range and the species Draba Aretioides in danger of extinction since the only place where it is found is in the high Andean moors of Ecuador. Therefore, greater care is recommended to the protected area since wild cattle presence has affected the vegetation of Los Ilinizas Ecological Reserve.